IN SILICO PROCENA BIORASPOLOŽIVOSTI, FARMAKOKINETIČKIH I TOKSIKOLOŠKIH OSOBINA MODULATORA NEUROTRANSMISIJE 5-HT7 RECEPTORA - Džodić, Predrag (Acta medicae Medianae, 2022)
Serotonic transmission is important for psychiatric disorders (depression, anxiety, schizophrenia and epilepsy). 5-HT7 receptors are a new therapeutic alternative in the treatment of psychiatric diseases, therefore there is a need to discover 5-HT7 receptor agonists and antagonists. For 38 selected compounds, 5-HT7 receptor neurotransmission modulators, bioavailability, pharmacokinetic and toxicological properties were assessed. Based on the calculations, 38 compounds (except compound 28) do not show more than one deviation from the Lipinski rule, and good absorption and permeability are possible after oral administration. Good blood-brain permeability was predicted for 29 tested compounds, while poor blood-brain permeability was predicted for 9 compounds. Moreover, 30 compounds exhibited inhibition of the CYP 450 3A4 isoenzyme, while 16 compounds were not a substrate for P-glycoprotein. The risk of mutagenicity is not shown by any of the tested compounds (except compounds 5, 22, 23). 35 tested compounds do not show the risk of carcinogenicity. Most of the 5-HT7 receptor modulators tested do not pose a risk for reproductive toxicity and irritant effect. Based on the obtained results for drug similarity parameters and pharmacokinetic properties, the tested 5-HT7 receptor modulators (compounds 1-38) should have good bioavailability after oral administration, as well as good blood-brain permeability (29 tested compounds). In vitro and in vivo studies of the tested 5-HT7 receptor modulators, exept for compounds 5, 11, 17, 22, 23, 34, could be performed to verify the results obtained because the tested compounds have the potential to be new drugs in the treatment of psychiatric diseases in the future.